Antibacterial activity of oregano essential oil against foodborne pathogens - Cattelan, Mariandacute;lia Goncandcedil;alves [UNESP]; de Castilhos, Maurício Bonatto Machado [UNESP]; Sales, Priscila Juliana Pinsetta [UNESP]; Hoffmann, Fernando Leite [UNESP] (Emerald, 2013)
Purpose: This paper aims to evaluate in vitro antibacterial activity of oregano essential oil against foodborne pathogens as a starting point for the use of spice as a natural preservative in food. Design/methodology/approach: Disc and well-diffusion assays were performed to investigate antibacterial activity of oregano essential oil against six bacteria strains: Bacillus cereus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella Typhimurium. Three concentrations of oregano essential oil were employed: 1.0 percent, 2.0 percent and 5.0 percent. Bacterial growth inhibition was determinate as the diameter of the inhibition zones. Findings: Oregano essential oil showed antibacterial activity against spoilage microorganisms, at different concentrations, except for P. aeruginosa. There was a significant difference between methodologies only for the microorganism S. aureus. The results provided evidence of the existence of significant differences among the concentrations of oregano essential oil for each microorganism evaluated. Research limitations/implications: Although the research for this paper involved only oregano essential oil, it provided a starting-point for further investigations concerning spices as natural preservatives for food systems. Practical implications: Disc and well-assays were found to be simple and reproducible practical methods. Other spices, their essential oil and extracts might be researched against other micro-organisms. Furthermore, in situ studies need to be performed to evaluate possible interactions between essential oils and compounds naturally present in food against microbial strains. Social implications: The imminent adoption of measures to reduce the use of additives in foods and the reduction on using such compounds. Originality/value: This study provides insights that suggest a promising exploratory development of food natural preservative against spoilage microorganisms in food systems by the use of oregano essential oil. © Emerald Group Publishing Limited.
Keywords: Antimicrobial; Essential oil; Food preservation; Foodborne; In vitro; Oils; Oregano